Strengths, innovation, and opportunities in a burgeoning industry: an exploratory study. Issue 2 (9th April 2018) - Duarte Alonso, Abel; Sakellarios, Nikolaos; Alexander, Nevil; O'Brien, Seamus
Abstract : Purpose: The purpose of this paper is to examine key areas related to the craft brewing industry from the perspective of operators of micro and small craft breweries, and propose a framework based on the resourced-based theory of the firm and the theory of innovation. The areas investigated include participants' perceived strengths of their craft brewery, involvement in innovative practices, opportunities for the craft brewing firm, and potential differences related to these areas based on the demographic characteristics of participants and their breweries. Design/methodology/approach: Given its growing significance and economic contribution, the US craft brewery industry was chosen for this study. An online questionnaire was designed to gather data from craft brewery operators across the nation. Findings: Product and service quality, knowledge, reputation, and expertise were revealed as key strengths, while creating new recipes and using social media tools were the most considered ways of innovating. Furthermore, opportunities were perceived through craft beer tourism, increased consumption, and quality improvements. Statistically significant differences emerged, particularly based on production levels, staff numbers, and involvement/no involvement in exports. Various associations between the findings and the adopted theoretical frameworks were revealed. Originality/value: In terms of originality, the proposed refinement based on the adopted theoretical frameworks and findings facilitates understanding of the significance of resources and innovation, particularly for firms operating in a growing industry. Regarding value, the findings have important implications for the industry, for instance, in the marketing of craft brewing, as well as in the development of new craft brewing products.